1964
DOI: 10.1152/ajplegacy.1964.207.2.286
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrical stimulation of telencephalon on ovulation and oviposition in the hen

Abstract: Electrical stimulation of the archistriatum and paleostriatum primitivum leads to a 2- to 4-hr delay of ovulation and generally to a delay of 2–48 hr of oviposition in White Leghorn hens. The optimal time for stimulation for obtaining these effects is 13–16 hr before ovulation. Electrical stimulation of the neostriatum, area septalis, or of the paleostriatum augmentatum affects neither ovulation nor oviposition. Possible explanations are offered for the effects observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1966
1966
1999
1999

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…the nest-coo in bilaterally OVX females (59). The ICo may also be important for controlling female quail tion and avoidance, fear and aggressive behaviours (64)(65)(66). Finally, sexual interactions induced FLI cells within the proceptive behaviour as suggested by the observation that, in the present study, the frequency of these behaviours was hyperstriatum ventrale (HV ) just lateral to the lateral ventricles and this activation was significantly correlated significantly correlated to ICo activation.…”
Section: Behavioural and Lh Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…the nest-coo in bilaterally OVX females (59). The ICo may also be important for controlling female quail tion and avoidance, fear and aggressive behaviours (64)(65)(66). Finally, sexual interactions induced FLI cells within the proceptive behaviour as suggested by the observation that, in the present study, the frequency of these behaviours was hyperstriatum ventrale (HV ) just lateral to the lateral ventricles and this activation was significantly correlated significantly correlated to ICo activation.…”
Section: Behavioural and Lh Resultssupporting
confidence: 60%
“…Proceptive behaviour of the female was nonetheless correlated with Fos activation in a neighbouring part of the archistriatum just lateral to the anterior commissure and occipitomesencephalic tract. The significance of this induction remains to be established, but it may be related to the activation of the limbic or sensorimotor system involved in copulatory performance as electrical stimulation of this region is associated with ovulation and avoidance, fear and aggressive behaviours ( 64–66).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, electrical stimulation studies in owls have indicated a role of archistriatal input to the striatum in the generation of head saccades (Masino and Knudsen, 1993). Finally, a variety of studies have shown that the archistriatum is important for a wide range of behaviors, from visually guided behavior to song control and feeding and from fear-and aggression-related behaviors to gastrointestinal functions and ovulation (Kalischer, 1905;Juhasz and van Tienhoven, 1964;Phillips, 1964;Zeier, 1971Zeier, , 1974. Whether these roles are mediated by projections to the striatum or by extratelencephalic projections is unknown.…”
Section: Archistriaturnmentioning
confidence: 99%
“…JuHASZ & VAN Tienhoven, 1964). In mammals telencephalic and limbic projections to the anterior hypothalamic region and to the reticular formation of the lower brain stem are well established.…”
Section: Telencephalic Effects On Periodic Autonomic Functionsmentioning
confidence: 99%